Regression discontinuity evidence on the effectiveness of the minimum legal e-cigarette purchasing age - Jeff DeSimone; Daniel Grossman; Nicolas R. Ziebarth (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Increases in youth vaping rates and concerns of a new generation of nicotine addicts recently prompted an increase in the federal minimum legal purchase age (MLPA) for tobacco products, including e-cigarettes, to 21 years. This study presents the first regression discontinuity evidence on the effectiveness of e-cigarette MLPA laws. Using data on 12th graders from Monitoring the Future, we obtain robust evidence that federal and state age-18 MLPAs decreased underage e-cigarette use by 15-20% and frequent use by 20-40%. These findings suggest that the age-21 federal MLPA could meaningfully reduce e-cigarette use among 18-20-year-olds.
Keywords: I12; I18; H51; H75; 330; e-cigarettes; minimum legal purchase age (MLPA); Monitoring the Future; regression discontinuity; vaping